Nitric oxide inhibition strategies - Wong, Vivian (Wai Chong) (Future Sci OA, 2015)
Nitric oxide is involved in many physiologic processes. There are efforts, described elsewhere in this volume, to deliver nitric oxide to tissues as a therapy. Nitric oxide also contributes to pathophysiologic processes. Inhibiting nitric oxide or its production can thus also be of therapeutic benefit. This article addresses such inhibitory strategies.